A New Application of the Sumudu Transform for the Falling Body Problem. (9th November 2021) - Akgül, Esra Karatas; Akgül, Ali; Alqahtani, Rubayyi T.
Abstract : In this study, we investigate the falling body problem with three different fractional derivatives. We acquire the solutions of the model by the Sumudu transform. We show the accuracy of the Sumudu transform by some theoretic results and implementations.